Characterization of Metal Tolerance Proteins and Functional Analysis of GmMTP8.1 Involved in Manganese Tolerance in Soybean - Li, Jifu; Dong, Rongshu; Jia, Yidan; Huang, Jie; Zou, Xiaoyan; An, Na; Song, Jianling; Chen, Zhijian (Frontiers in Plant Science, 2021)
Manganese (Mn) is an essential micronutrient for plant growth, but can be toxic to plants when it reaches excessive levels. Although the metal tolerance proteins (MTPs), which belong to the cation diffusion facilitator (CDF) family, have been demonstrated to play critical roles in Mn tolerance in plants, the characteristics and functions of GmMTP members in the response of soybean (Glycine max) to Mn toxicity have not been documented. In this study, growth inhibition was observed in soybean plants that were exposed to toxic level of Mn in hydroponics, as reflected by the generation of brown spots, and decreased leaf chlorophyll concentration and plant fresh weight. Subsequent genome-wide analysis resulted in the identification of a total of 14 GmMTP genes in the soybean genome. Among these GmMTPs, nine and twelve GmMTPs were found to be regulated by excess Mn in leaves and roots, respectively. Furthermore, the function of GmMTP8.1, a Mn-CDF homologue of ShMTP8 identified in the legume Stylosanthes hamata that is involved in Mn detoxification, was characterized. Subcellular localization analysis showed that GmMTP8.1 was localized to the endoplasmic reticulum (ER). Heterologous expression of GmMTP8.1 led to restore the growth of the Mn-hypersensitive yeast (Saccharomyces cerevisiae) mutant Δpmr1, which is defective in Mn transport into the Golgi apparatus by a P-type Ca/Mn-ATPase. Furthermore, GmMTP8.1 overexpression conferred tolerance to toxic level of Mn in Arabidopsis (Arabidopsis thaliana). Under excess Mn condition, concentrations of Mn in shoots but not roots were decreased in transgenic Arabidopsis overexpressing GmMTP8.1 compared to the wild type. Overexpression of GmMTP8.1 also led to up-regulation of several transporter genes responsible for Mn efflux and sequestration in Arabidopsis, including AtMTP8/11. Taken together, these results suggest that GmMTP8.1 is an ER-localized Mn transporter contributing to confer Mn tolerance by stimulating export of Mn out of leaf cells and increasing sequestration of Mn into intracellular compartments.